1985
DOI: 10.1182/blood.v65.3.644.bloodjournal653644
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hairy cell leukemia with recombinant alpha 2 interferon

Abstract: Nine patients with progressive hairy cell leukemia were treated with subcutaneous injections of recombinant alpha 2 interferon (2 to 10 X 10(6) U/m2) three times weekly. Eight patients completed at least eight weeks of treatment and were evaluable; one patient with refractory thrombocytopenia died of an intracerebral hemorrhage after two doses of interferon. Seven of eight patients responded, with responses occurring as early as two weeks. Four patients also had resolution of their monocytopenia. No complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, in many cases, IFN has been replaced or relegated to therapy in second-line treatment by the development of novel reagents or combinations (Goldman et al 2003). IFN-α treatment resulted in substantial and sustained improvement in granulocyte, platelet counts, and hemoglobin levels in 77% of treated patients with HCL and at least some improvement in minor responses occurred in 90% (Ratain et al 1985). The percentage of patients with HCL who required blood cell or platelet transfusions decreased significantly during treatment.…”
Section: Type I Ifnsmentioning
confidence: 99%
“…However, in many cases, IFN has been replaced or relegated to therapy in second-line treatment by the development of novel reagents or combinations (Goldman et al 2003). IFN-α treatment resulted in substantial and sustained improvement in granulocyte, platelet counts, and hemoglobin levels in 77% of treated patients with HCL and at least some improvement in minor responses occurred in 90% (Ratain et al 1985). The percentage of patients with HCL who required blood cell or platelet transfusions decreased significantly during treatment.…”
Section: Type I Ifnsmentioning
confidence: 99%
“…We and other investigators have reported excellent ,responses for patients with hairy-cell leukemia treated with recombinant leukocyte A interferon [43][44][45][46]. Responses appear to be equivalent for patients who have not had prior splenectomy.…”
Section: Interferonmentioning
confidence: 59%